The Plea for the Reapropriation of Nature: Towards the New Forms of Biotechnological Capital - Valdebenito González, María Paz (Sociedad y Economía, 2013)
Abstract: This paper analyzes the relation between nature and society within the frameworkof the new biotechnological productions, through a critical assessment of modernbiotechnological interventions into Nature. Biotechnology allows a reinvention ofthe Capitalist System in the context of a strong Environmental Globalization and the requirementof a longed ecological balance. This reinvention emerges from a re-appropriationof Nature based in scientific knowledge and a symbolic operation which, throughthe discourse of sustainable development, reshapes the concept of nature to meet therequirements of standardization, control and capitalization, under market and capitalneeds.